Enhanced differentiation of 3T3-L1 adipocytes by extracts of Pleurotus giganteus (Berk) Karunarathna & K.D. Hyde / Puvaneswari Paravamsivam - Puvaneswari , Paravamsivam (2017)
Pleurotus giganteus (Berk.) Karunarathna & K. D. Hyde is a culinary mushroom that has been consumed by the indigenous communities in Peninsular Malaysia for hundreds of years. Although large scale domestication of this wild mushroom is currently in progress, the findings on its medicinal properties are very limited. This study was conducted to evaluate the insulin-sensitising capabilities of P. giganteus by using the 3T3-L1 cell line model. The basidiocarps of P. giganteus were purchased from Nas Agro Farm, Sepang and extracted using hot water and methanol. The methanol extract of P. giganteus was fractionated to obtain the hexane, butanol and ethyl acetate fractions. The effect of P. giganteus extracts and fractions on the proliferation of 3T3- L1 preadipocyte cells was assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Highest 3T3-L1 preadipocytes proliferation was obtained using hot water extract and butanol fraction of P. giganteus. Methanol extract and hexane and ethyl acetate fractions caused moderate proliferation of preadipocytes respectively. Subsequently, Oil Red O assay was carried out to investigate the effect of P. giganteus extracts and fractions on lipogenesis during adipocyte differentiation of 3T3-L1 cells. Ethyl acetate fraction at 100 μg/ml stimulated the highest lipid accumulation at 175.30 ± 2.7%. The glucose uptake of differentiated 3T3-L1 cells was measured by fluorescence based glucose uptake assay. The highest glucose uptake was recorded at 136.20 ± 10.5% in ethyl acetate fraction at 100 μg/ml respectively. The lipolysis of differentiated 3T3-L1 adipocytes was measured using ZenBio’s nonesterified fatty acid and glycerol quantification kit. The ethyl acetate fraction at 100 μg/ml showed the highest free fatty acid release from 3T3-L1 adipocytes by 3.4 fold. Collectively, the ethyl acetate fraction at 100 μg/ml moderately induced cell proliferation of 3T3-L1 preadipocyte cells and highly stimulated lipogenesis, glucose uptake and lipolysis in 3T3-L1 adipocytes. Therefore, ethyl acetate fraction was selected to study for its effect on 3T3-L1 adipocytes at a molecular level. The gene expression quantification was done using real time PCR analysis with TaqMan® primer. Ethyl acetate fraction of P. giganteus significantly enhanced adipogenic differentiation in 3T3-L1 adipocytes via the upregulation of SREBP, PPARγ and Pi3k genes. The glucose uptake was facilitated by the highly expressed glucose transporters, namely, glut 1 and glut 4. These results suggest that ethyl acetate fraction of P. giganteus has insulin sensitising effect on adipocytes and therefore has the potential to act as an adjuvant for the management of type 2 diabetes.